A placebo controlled randomized clinical trial of Crocus sativus L. (saffron) on depression and food craving among overweight women with mild to moderate depression. (10th October 2019) - Akhondzadeh, Shahin; Mostafavi, Seyed‐Ali; Keshavarz, Seyed Ali; Mohammadi, Mohammad Reza; Hosseini, Saeed; Eshraghian, Mohammad Reza
Abstract: What is known and objective: Crocus sativus L., commonly known as saffron, has known anti‐depressive properties. However, its effects on food craving and body weight in depressed patients are unknown. Hence, we aimed to evaluate the effects of saffron capsules on food craving, body weight and depression among overweight women with mild and moderate depression compared to the placebo. Methods: Seventy‐three women with BMI ≥ 25 comorbid with mild‐to‐moderate depression were recruited in this 12‐week double‐blind, placebo‐controlled randomized clinical trial. Participants were randomly assigned into one of the two groups receiving daily either 30 mg of Crocus sativus capsules (15 mg twice/day) or placebo capsules (twice/day). We performed body composition assessments, and beck depression inventory‐II at the baseline, and then 2, 4, 8 and 12 weeks later. One month after the participants stopped taking the capsules, weight differences were measured and compared between groups. Results and discussion: Fifty‐two patients finished the study. The demographic and clinical variables at baseline were the same in two groups. Mean depression scores in the saffron group significantly decreased compared to placebo (mean ± SD: −8.4 score ± 5.9 vs −3.9 ± 5.5; t [50] = 2; P  = .007; 95% CI: 1.3‐7.7). There was not a significant effect of saffron on food craving using repeated‐measures ANOVA, F (1, 29) = 0.38, P  = .54. Patients in the saffron group showed fewer side effects. What is new and conclusion: Saffron capsules were not effective in reducing food craving, but as a safe over‐the‐counter supplement, it may help reduce the symptoms of depression in patients who experience mild or moderate depression and are overweight. Abstract : Women with BMI ≥ 25 comorbid with mild‐to‐moderate depression were randomly assigned into one of the two groups receiving daily either 30 mg of saffron capsules (15 mg twice/day) or placebo capsules (twice/day) for 12 weeks. Mean depression scores in the saffron group significantly decreased compared to placebo, while there was not a significant effect of saffron on food craving during the study.